Ruch: kinowość w malarstwie i literaturze - Bal, Mieke; Lipiński, Filip (Artium Quaestiones, 2020)
Translation of Mieke Bal's chapter into Polish. Translation of a fragment of Mieke Bal's book Emma & Edvard Looking Sideways: Loneliness and the Cinematic (2017), which accompanied an exhibition of Edward Munch’s painting in Munch Museum in Oslo. Bal analyzes Munch’s work in terms of its cinematic quality offering a persuasive argument about the productiveness of such an approach. Her perspective is framed by diverse notions of movement, inspired by readings of Henri Bergson’s philosophy. Following the set-up of the exhibition, which included her and Michelle Williams Gamaker’s video-installation Madame B., based on Gustave Flaubert’s novel Madame Bovary, she incorporates in her account aspects of cinematic thinking in Flaubert’s literature and discusses a dialogue between Munch’s work and their installation. Finally, Bal talks about the political dimension of movement in art, happening between the artwork and the viewer.